Application of response surface methodology in pes/speek blend NF membrane for dyeing solution treatment - Lau, W. J. (Techno Press, 2010)
In this study, response surface methodology (RSM) was performed in NF membrane process to evaluate the separation efficiency of membrane in the removal of salt and reactive dye by varying different variables such as pressure, temperature, pH, dye concentration and salt concentration. The significant level of both the main effects and the interaction were observed by analysis of variance (ANOVA) approach. Based on the statistical analysis, the results have provided valuable information on the relationship between these variables and the performances of membrane. The rejection of salt was found to be greatly influenced by pressure, pH and salt concentration whereas the dye rejection was relatively constant in between 96.22 and 99.43% regardless of the changes in the variables. The water flux on the other hand was found to be affected by the pressure and salt concentration. It is also found that the model predictions were in good agreement with the experimental data, indicating the validity of these models in predicting membrane performances prior to the real filtration process.